Development of digital science literacy based on Articulate Storyline based on objects’ material for class VIII junior high school - Setiawan, Agung Mulyo; Rahman, Fardian Novandi (Jurnal Inovasi Teknologi Pendidikan, 2025)
One solution to overcome the low quality of Indonesian education is to innovate education by developing digital tools for learning. Based on a literature review, digital tools in the form of Articulate Storyline software have many advantages in science learning, especially physics. Therefore, the development of students’ digital science literacy based on an Articulate Storyline material on force on objects for grade VIII junior high school students is important. The purpose of this study was to determine the level of validity and feasibility of Articulate Storyline as a learning medium to develop students’ digital science literacy. The method used to develop this media uses 4D (Define, Design, Develop, and Disseminate). Data collection techniques for media validity use media, material, and readability validation instruments, while for students’ digital science literacy skills, use practice questions and questionnaires. As supporting data, we also conducted interviews, which were then analyzed descriptively. Respondents in this study were expert validators (Lecturers), Teachers, and Students. The results we obtained showed that (a) the results of the validity of the media, materials, and readability were declared ’very valid’ with values ​​of 89.4%, 100%, and 75.8%; and (b) the students’ digital science literacy skills was declared ’very good’ with a value of 80.0. These results indicate that the development of digital science literacy based on Articulate Storyline is worthy of being developed as an innovative learning medium. We recommend that digital science literacy be developed in other science materials, such as biology and chemistry.